2008
DOI: 10.1097/01.nnr.0000313504.37970.f9
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Time Pressure and Experience on Nurses' Risk Assessment Decisions

Abstract: Time pressure reduced nurses' ability to detect the need and the tendency to report intervening. Thus, there were more failures to report appropriate intervention under time pressure, and the positive effects of clinical experience were negated under time pressure. More and larger scale research on the effect on clinical outcomes of time pressured nursing choices is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 30 publications
(20 reference statements)
1
50
1
2
Order By: Relevance
“…This study's heavy workload measure includes items associated with nurse perceptions of time pressure, or not enough time to get work done (e.g., arriving early/leaving late, missing breaks, too much work to do). In one simulated study of nurses' decision-making performance, time pressure negatively influenced nurses' capacity to detect the need for intervention, resulting in failure to rescue [37]. Of note is that under conditions without time pressure, nurses with clinical expertise performed better than novice nurses; the positive effects of clinical expertise, however, were negated when time pressure was introduced to clinical simulations [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study's heavy workload measure includes items associated with nurse perceptions of time pressure, or not enough time to get work done (e.g., arriving early/leaving late, missing breaks, too much work to do). In one simulated study of nurses' decision-making performance, time pressure negatively influenced nurses' capacity to detect the need for intervention, resulting in failure to rescue [37]. Of note is that under conditions without time pressure, nurses with clinical expertise performed better than novice nurses; the positive effects of clinical expertise, however, were negated when time pressure was introduced to clinical simulations [37].…”
Section: Discussionmentioning
confidence: 99%
“…In one simulated study of nurses' decision-making performance, time pressure negatively influenced nurses' capacity to detect the need for intervention, resulting in failure to rescue [37]. Of note is that under conditions without time pressure, nurses with clinical expertise performed better than novice nurses; the positive effects of clinical expertise, however, were negated when time pressure was introduced to clinical simulations [37]. The European Nurses' Early Exit study surveyed over 61,000 nurses [38].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study revealed that experience is one of the main factors that determine the nurses' ability to take decisions. Clinical experience where found to positively strengthen nursing care [13] [20]. Through experience, the critical care nurses become more aware of their role in decision-making process.…”
Section: Discussionmentioning
confidence: 99%
“…The difficult and complicated health situation in critical care areas highlight the complexity and the importance of nurses decision making [14]. Patients in critical care units are seriously ill and frequently unstable and their health changed rapidly [14] [19] [20]. These changes require the nurses to make decisions in a limited period of time [4].…”
Section: Discussionmentioning
confidence: 99%
“…From traders in the stock market to consumers in a store, many real-world decisions are made under time pressure (e.g., Bourgeois & Eisenhardt, 1988;Dhar & Nowls, 1999;Roth & Ockenfels, 2002;Thompson et al, 2008). This time pressure can alter many facets of decision-making, potentially making people more impulsive, defensive, or stressed, and occasionally more risk seeking (Ariely & Zakay, 2001;Dror, Busemeyer, & Basola, 1999;Gladstein & Reilly, 1985;Kelly & Karau, 1999;Nursimulu & Bossaerts, 2014;Zakay & Wooler, 1984).…”
Section: Introductionmentioning
confidence: 99%